Analysis of fire risk and fire management in the Bilibiza Administrative Post, Mozambique - Máquina, Dalmildo Agostinho; Daude, Ivan Abdul; Jeremias, Adérito da Silva; Serrote, Caetano Miguel Lemos; Mussalama, Adélio Zeca (Revista Ecologia e Nutrição Florestal - ENFLO, 2023)
Forest fires contribute to forests degradation. For this reason, it is essential to know the factors that favour its occurrence and map susceptible areas to allow the development of specific programs for fire management. In this study, we used Geographic Information Systems to analyze the risk of fire occurrence in the Administrative Post of Bilibiza, in Cabo Delgado province, Mozambique, in order to allow its management. Risk maps were produced based on variables that affect fire occurrence and spread through the Hierarchical Analysis Process method. Eighty households from three localities were also surveyed. Most of the area (78%) has a moderate risk of fire, 13% has high risk and 9% has low risk. Practices that influence fire frequency are hunting (85%), agriculture 82% and charcoal production (47%). About 84% of the community has neither knowledge nor information about national law regarding fire management. Awareness campaigns should be promoted to reduce fire occurrences in the Administrative Post of Bilibiza.